Peningkatan Efisiensi Bahan Bakar Melalui Redesain Aerodinamis Bodi Bus Dengan Metode Simulasi Computational Fluid Dynamics - Defryan Yusuf; Leonardo Paksi Sukoco (Infotekmesin, 2025)
Buses are generally designed with an emphasis on aesthetics. However, the design also needs to consider aerodynamic performance factors, as they directly affect vehicle stability, fuel efficiency, and emissions levels. This study proposes an aerodynamic redesign of the bus body to reduce fuel consumption. The expected values can be calculated using two more targeted design models with the assistance of SolidWorks and Computational Fluid Dynamics (CFD) simulation method. This method was used to evaluate the influence of body design on vehicle performance. Results show that the conventional bus consumes 30,016.17 kJ/year, while the redesigned bus only consumes 21,935.79 kJ/year, with a 26.93% reduction in fuel consumption. Additionally, the redesigned bus exhibits a lower drag coefficient, drag force, and energy input, indicating the effectiveness of the aerodynamic improvements.